1981
DOI: 10.1007/bf01982463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary histidine on tissue histamine concentration, histidine decarboxylase and histamine methyltransferase activity in the rat

Abstract: Three-week-old male rats were fed for two weeks diets supplying inadequate, adequate, or excess amounts of histidine. After the 2-week feeding of the experimental diets, the rats were killed. Brain, gastrocnemius muscle, kidney and stomach were removed and analyzed for histamine and free-histidine as well as for the degradative enzyme, HMT, and the histamine-synthesizing enzyme HDC. The following results were obtained: As the levels of dietary histidine increased, (1) tissue concentrations of free-histidine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Supplemental histidine may have the potential to increase histamine production by gastric enterochromaffin cells and by mast cells. Indeed, one rat study has found that stomach levels of histamine are increased as histidine intake increases beyond normal dietary levels 49. Hence, in susceptible individuals, supplemental histidine could conceivably increase risk for peptic ulcers by boosting gastric acid secretion.…”
Section: Cautionsmentioning
confidence: 99%
“…Supplemental histidine may have the potential to increase histamine production by gastric enterochromaffin cells and by mast cells. Indeed, one rat study has found that stomach levels of histamine are increased as histidine intake increases beyond normal dietary levels 49. Hence, in susceptible individuals, supplemental histidine could conceivably increase risk for peptic ulcers by boosting gastric acid secretion.…”
Section: Cautionsmentioning
confidence: 99%
“…As was shown in a study with rats, the histamine content of many tissues was found to be in correlation with the histidine amount in the diet [17]. It is not impossible that this phenomenon plays also a role in man.…”
Section: Discussionmentioning
confidence: 88%
“…Unexpectedly, the compensatory increase of Hdc expression was not observed in the LHD group. A previous study showed that an increase in dietary histidine enhanced Hdc enzymatic activity (41), suggesting that histidine itself might induce Hdc expression. The decreased histidine concentration in the cortex might reduce the expression of Hdc, although further studies are necessary to elucidate the mechanism of the mRNA expression.…”
Section: Downloaded Frommentioning
confidence: 99%